DECISION SUPPORT SYSTEM FOR SELECTING EDUCATIVE EQUIPMENT SUPPLIERS IN TOKO ANDA V7 - Sovia, Rini; Rani, Maha; Ardiansyah, Ricki; Rahman, Muhammad Aidil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: Toko Anda v7 is a shop that sells office stationery and school teaching aids. One of the items frequently ordered at Toko Anda v7 is educational teaching aids (APE). So that shop activities can continue to run, suppliers have a very important role, for this reason the supplier selection process is one of the important decisions that must be taken by the shop. However, this is a problem because each supplier has its own advantages and disadvantages. To help Toko Anda v7 in choosing suppliers, a decision support system was designed. The decision support system is able to provide alternative decision options that can be chosen by decision makers in Toko Anda v7 in determining suppliers of educational teaching aids. The method used in the decision selection process in this decision support system is Weighted Product (WP). Calculations using the Weighted Product (WP) method are able to provide decisions with fast and efficient calculations. The results of designing this decision support system are able to provide a ranking of alternative suppliers based on predetermined criteria. Keywords: Decision Support System; Supplier; Weighted Product Abstrak: Toko Anda v7 adalah toko yang bergerak dalam penjualan alat tulis kantor dan alat peraga sekolah. salah satu barang yang sering dipesan di Toko Anda v7 adalah alat peraga edukatif (APE). agar aktivitas toko tetap dapat berjalan suplier memiliki peran yang sangat penting, untuk itu proses pemilihan suplier menjadi salah satu keputusan yang penting yang harus diambil oleh toko. namun hal tersebut menjadi masalah karena setiap suplier memiliki kelebihan dan kekurangan masing-masing. untuk membantu Toko Anda v7 dalam memilih suplier maka dirancanglah sebuah sistem penunjang keputusan. sistem penunjang keputusan mampu memberikan pilihan alternatif keputusan yang bisa dipilih oleh pembuat keputusan di Toko Anda v7 dalam menentukan suplier alat peraga edukatif. metode yang digunakan dalam proses pemilihan keputusan di sistem penunjang keputusan ini adalah Weighted Product (WP). Perhitungan dengan metode Weigthted Product (WP) mampu memberikan keputusan dengan perhitungan yang cepat dan efisien. hasil dari perencangan sistem penunjang keputusan ini mampu memberikan perangkingan alternatif suplier berdasarkan kriteria-kriteria yang telah ditentukan. Kata kunci: Pemasok; Sistem Penunjang Keputusan; Weighted Product